Relations Between Students' Perceptions of Teacher Feedback and Intelligence Beliefs - Baumann, Amanda (My University, 2014)
Research suggests that students who endorse malleable intelligence beliefs demonstrate higher achievement and more positive academic self-perceptions than students who endorse fixed intelligence beliefs. Research also suggests that when teachers provide effort praise students are more likely to endorse malleable intelligence beliefs. The purpose of this study was to examine whether or not 4th and 5th grade students' intelligence beliefs and academic self-concepts change across time, and whether or not students' perceptions of their teachers' praise is related to intelligence beliefs and academic self-concept. Using a pre- and post-test study design, students from four classrooms (two from 4th grade, and two from 5th grade) were administered surveys that assessed their perceptions of teacher praise (either ability praise or effort praise), their beliefs about intelligence (either malleable or fixed), and their academic self-concepts. Surveys were administered at the beginning of the academic year and again in the middle of the academic year. The results of this study revealed that there was no significant difference between pre-test and post-test intelligence beliefs, nor was there a difference between pre-test and post-test academic self-concepts. Further, there were no significant relationships among perceived teacher praise, intelligence beliefs, and academic self-concepts.
Thesis (Educational Specialist in School Psychology)
Keywords: Academic achievement--Psychological aspects; Academic achievement--Social aspects; Praise--Educational aspects; Self-perception; Learning, Psychology of; Education, Elementary--Psychological aspects